Detection of Edwardsiella ictaluri infection in Tra catfish in Vietnam by polymerase chain reaction - Huyền, Trần Thị Thanh; Trung, Nguyễn Thị; Hải, Trương Nam (Vietnam Journal of Biotechnology, 2012)
Nowadays, Tra and Basa catfish infected with lesion white diseases internal organs are widespread in Viet Nam, one of prevalent pathogenic agents is Edwardsiella ictaluri. It is a constant threat to the sustainability and economic viability of aquaculture. Early diagnosis plays a vital role in management of Tra catfish disease not only in Vietnam but also in all over the world. In this report, the polymerase chain reaction that amplifies DNA with high specificity and rapidity was evaluated for rapid detection of E. ictaluri. The primers were designed specifically to recognize the eip18 gene of this pathogen, which band size is 480 bp. The results showed that DNA of E. ictaluri could be amplified distinctly by using these primers. These primers amplified eip18 gene of E. ictaluri, yeilding a product of 480 bp, and did not amplify E. tadar and other pathogenic agents such as E. coli, Proteus, Salmonella. In addition, this technique could amplify this gene with high specificity and sensitivity (3 cfu/ml). Thus, we concluded that the PCR could potentially be used for rapid diagnosis E. ictaluri.